Endoscopic ultrasound-guided gastroenterostomy versus surgical gastrojejunostomy for the palliation of gastric outlet obstruction in patients with peritoneal carcinomatosis - Abbas, Ali; Dolan, Russell D.; Bazarbashi, Ahmad Najdat; Thompson, Christopher C. (Endoscopy, 2022)
Background Gastric outlet obstruction (GOO) with peritoneal carcinomatosis presents a technical challenge. Surgical gastrojejunostomy (SGJ) or enteral stenting have been the standard of care; however, endoscopic ultrasound-guided gastroenterostomy (EUS-GE) has emerged as a favorable alternative. Few data exist that compare these techniques in the setting of peritoneal carcinomatosis.Methods This single-center retrospective cohort study included 25 EUS-GE and 27 SGJ consecutive patients. Baseline demographics, cancer diagnosis and stage, clinical and technical success, adverse events, and obstruction recurrence data were collected. The primary outcome was the technical success comparison; secondary outcome was the adverse event rate comparison. Rates were compared with standard statistical tests.Results Mean age, obstruction location, and symptoms were similar between the groups. The EUS-GE group had more advanced disease (clinical stage 4, 100 % vs. 67 %; P = 0.006) and higher American Society of Anesthesiologists classification (class 3–4, 92 % vs. 50 %; P = 0.004). The technical success rate was 100 % in both groups (P > 0.99) and the adverse event rate was lower for EUS-GE (8 % vs. 41 %; P = 0.01). Clinical success was 88 % for EUS-GE and 85 % for SGJ (P > 0.99) and recurrent obstruction was lower with EUS-GE (28 % vs. 41 %; P = 0.13). The EUS-GE group had shorter procedure duration, length of stay, and time to chemotherapy resumption than the SGJ group.Conclusions Although the EUS-GE group was older, with more comorbidity and advanced stages, the technical success rate was similar to SGJ and it had significantly fewer adverse events. EUS-GE is a safe and effective option for the management of malignant GOO with peritoneal carcinomatosis.